Development of Interactive Arabic Language Learning Evaluation Media Using the Wordwall Platform for Students at MIN 1 Malang - Sundirah, Sundirah; Sutaman, Sutaman; Hilmi, Danial (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Evaluation is one of the essential components in the learning process. It aims to obtain accurate information regarding students' achievements based on predetermined indicators. To facilitate the implementation of evaluation for teachers, an assessment tool that is accurate, efficient, and interactive is required. However, the evaluation tools commonly used are still conventional in nature, making the process appear monotonous and often causing students to feel bored and less engaged. As a result, student participation in the evaluation process tends to be low. To address this issue, the researcher aims to develop and describe the feasibility of an Arabic language learning evaluation media based on the Wordwall platform for fifth-grade students at MIN 1 Malang City. The research employed a Research and Development (RD) approach using the ADDIE model. Data were collected through observation, interviews, documentation, and questionnaires, and were analyzed both qualitatively and quantitatively. The research findings indicate that the Wordwall-based evaluation media is highly valid, with validation scores of 84% from media experts, 93% from material experts, and 100% from the classroom teacher. Student responses were also highly positive, with an interest level of 100%. Therefore, this media is considered feasible and engaging for use in Arabic language learning evaluation.